The Effect of RRA Heat Treatment on the Intergranular Corrosion (IGC) of the AA7075 Alloy - Ozer, G.; Karaaslan, A. (CARL HANSER VERLAG, 2017)
In this study, the effects of retrogression and re-aging (RRA) heat treatment applied on AA7075 aluminum alloy at various times and temperatures on the intergranular corrosion (IGC) behavior were investigated. The IGC solution was prepared according to ASTM G110-92 standard and the samples were kept in the solution for 24 hours. Susceptibility of the alloy to IGC was determined by weight loss detection, macro and microstructure studies. Scanning electron microscope (SEM) analysis was also performed. According to the results obtained, it was determined that the RRA processes in the AA7075 alloy change the grain boundary morphology and decrease the IGC corrosion susceptibility.
Keywords: ZN-MG ALLOY; Metallurgy & Metallurgical Engineering